Vietnam Inequalities in Health, Nutrition and Population - Oomman, Nandini (World Bank, Washington, DC, 2018)
This paper focuses on the inequalities in health, nutrition, and population in Vietnam. It presents data on disaggregated health status and health services utilization that is organized by asset or wealth quintiles, a form that enables readers to better understand the distribution of these indicators from the poorest sections to the richest sections of society. That is, the profile takes data on population as well as on reproductive and child health and nutrition from tables presented in the Vietnam version of Socio-Economic Differences in Health, Nutrition and Population (Gwatkin, Rustein, Johnson, Pande and Wagstaff, 2000) and presents them in a more easily accessible format designed to call attention to the inequalities that exist among socioeconomic groups. These kinds of disaggregated data have great potential value for the design and implementation of efforts to achieve the Millennium Development Goals (MDGs) for health in a manner that can bring about the greatest possible gains for the poor. By focusing attention on the problems suffered by the disadvantaged groups that are of greatest concern, these data can increase the likelihood that MDG initiatives will effectively deal with those problems and reach those groups. The profile also provides evidence of successful interventions that have reached those who are poor. The hope is that this attention will stimulate thought about how best to reach the neediest groups with health services and other programs.